Analisis Sentimen Perdebatan Publik Tentang Khilafah Di Twitter (Studi Pada Data Twitter Pada Topik Percakapan Khilafah Tahun 2022) - Hudha, Noor; Kalaloi, Abdul Fadli (eProceedings of Management, 2024)
Conversations about the Caliphate are quite massive and widely discussed in the world. The purpose of this study isto find out how the general public perceives the Caliphate as seen from sentimens on Twitter. Public conversationsabout Khilafah are often linked to radicalism and terrorism. On the other hand, public conversations about theKhilafah also arise because there are people who want to restore the Khilafah system in the world. This researchmethod uses a qualitative method with a descriptive sentimen analysis approach using data sources obtained from anopen source crawling website called academic.droneemprit.id. The sentimen results based on theacademic.droneemprit.id site are 60% of conversations discussing Khilafah in Indonesia are positive sentimens, 38%convey negative sentimens, and 3% convey neutral sentimens. The majority of tweets discussing the Khilafah issueare positive tweets. However, tweets that are popular and have high engagement are negative tweets. Keywords-sentimen analysis, public debate, caliphate, Twitter.